Regeneration of selected callus of three potato cultivars (Solanum tuberosum.L) and studying their tolerance to drought stress - Lama Abdullah Laila; Salim Hussein Zaid; Fahed Al-Biski; Abdulkarim Dakah (BMC Plant Biology)
Abstract Drought stress poses a significant threat to potato production in Syria, necessitating the development of resilient cultivars. This study, conducted at the Plant Biotechnology Laboratory of the National Commission for Biotechnology in Damascus, investigated the impact of drought stress on key growth parameters of regenerated somaclones derived from selected callus of three potato cultivars (Solanum tuberosum L.): Salvador, Yalas, and Arizona. The research revealed striking differences in regeneration efficiency among cultivars. Yalas exhibited the highest somaclone regeneration rate at 32.1% when cultured on medium supplemented with 25 mg·L⁻1 adenine sulfate and 1.5 mg·L⁻1 BAP. Salvador and Arizona followed with regeneration rates of 21.4% and 14.5%, respectively, using 15 mg·L⁻1 adenine sulfate plus 1.5 mg·L⁻1 BAP. Comprehensive analysis of growth indicators (including plant height, leaf number and area, and root number and length) under drought stress conditions identified superior drought-tolerant somaclones. Notably, Y3 and Y2 (Yalas), S3 and S6 (Salvador), and A1 (Arizona) demonstrated exceptional drought resilience across multiple growth parameters. These findings provide valuable insights for potato breeding programs aimed at enhancing drought tolerance, potentially mitigating the impact of water scarcity on potato production in Syria and similar arid regions.